KONTROL DIRI, RELIGIUSITAS, LITERASI KEUANGAN, INKLUSI KEUANGAN DAN PENGARUHNYA TERHADAP PERILAKU MENABUNG ANGGOTA KOPERASI KOPDIT SUBE HUTER - Loar, Theresia Maria Dua; Mitan, Wilhelmina; Rangga, Yoseph Darius Purnama (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This research aimed to determine whether self-control, religiosity, financial literacy, and financial inclusion influence the savings behaviour of Sube Huter Credit Union members. The data collection techniques used in this research were observation, questionnaires, interviews, and documentation. This research used quantitative data with a causal approach. The results of the research showed that (1) self-control did not affect the saving behaviour of Sube Huter Credit Union members, (2) religiosity did not affect the saving behaviour of Sube Huter Credit Union members, (3) financial literacy had a positive and significant effect on the saving behaviour of Sube Huter Credit Union members, and (4) financial inclusion had a positive and significant effect on the saving behaviour of members of the Sube Huter Credit Union. The influence of self-control, religiosity, financial literacy, and financial inclusion on the saving behaviour of members of the Sube Huter Credit Union was 58%, while 41,6% was influenced by other factors outside the research variables.